Recruitment of the hadith of the Prophet in the poetry of Abu Ishaq al-Ilbiri - Hattab , Salman; Mari , Rodan; Kababah , Ghousen (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research attempts to shed light on the use of the Prophet's Hadith in the poetry of Abu Ishaq Al-Ilbiri, and on the sources of quotation and the disclosure of the religious influence in his poetry,and the implications resulting from this recruitment, and the statement of its role in the service of the poet's experience of asceticism and its ability to excite and influence. In addition to the intended of the poet,the Hadith has represented a rich material contributed to the enrichment of the poetic text, and help him to convey the meaning he wants.